The impact of COVID-19 on real estate markets in Germany - Eyayaw Beze; Patrick Thiel (German Economic Review (GER), 2025)
The COVID-19 pandemic has disrupted established urban patterns. The literature on the impact of the pandemic on the US housing market has shown a significant increase in the demand for suburban housing, resulting in a considerable increase in suburban prices compared to those in the city center (termed the "donut effect"). However, the German housing market did not experience such drastic changes. To examine price and rent adjustments during the pandemic, we analyze detailed housing data and find little evidence supporting the donut effect seen in the US. Apartment rents increase in suburban areas, while house prices do not change significantly. Examining the role of amenities, we find no explanation for price and rent differences between the central business district (CBD) and suburbs. The differences between the two markets may be attributed to cultural and structural distinctions. Our analysis, which includes data on population patterns and migration behavior, reveals that residents in Germany exhibit a slower-moving trend. Our findings remain robust across different settings and subsets of cities.
Keywords: R23; R31; 330; amenities; COVID-19; donut effect; house prices; rent gradient